Protodammara reimatamoriori, a new species of conifer (Cupressaceae) from the Upper Cretaceous Tupuangi Formation, Chatham Islands, Zealandia. Issue 1 (2nd January 2019) - Mays, Chris; Cantrill, David J.
Abstract : Mays, C. & Cantrill, D.J., 4 January 2018. Protodammara reimatamoriori, a new species of conifer (Cupressaceae) from the Upper Cretaceous Tupuangi Formation, Chatham Islands, Zealandia. Alcheringa 43, , 114–126. ISSN 0311-5518. Isolated conifer female reproductive structures are common fossil elements from Cenomanian ( ca 99–94 Ma) charcoal- and resin-rich beds of the Tupuangi Formation, Chatham Islands, southwest Pacific Ocean. Recent findings have proposed that these are the oldest fossil evidence of serotiny, a highly successful fire-adaptive reproductive strategy common among tree species living in fire-prone areas today. Herein, we systematically describe the external morphological and anatomical features of these fossils, by employing a combination of manual extraction and neutron tomography techniques. We propose a new species of conifer, Protodammara reimatamoriori, and a re-examination of fossil material of the Protodammara type species facilitated an emendation of the genus. Protodammara shares numerous features with extant Cunninghamia, Taiwania, Athrotaxis, and several extinct taxa of Cupressaceae, and is interpreted as an extinct lineage of the early-divergent 'taxodioid Cupressaceae' stem group. Chris Mays [ chris.mays@nrm.se ] Department of Palaeobiology, Swedish Museum of Natural History, Frescativägen 40, Stockholm 114 18, Sweden; School of Earth, Atmosphere and Environment, Monash University, 9 Rainforest Walk, Clayton, VIC 3800, Australia; David J. Cantrill [ david.cantrill@rbg.vic.gov.au ] Royal Botanic Gardens Victoria, Private Bag 2000, South Yarra, VIC 3141, Australia; School of BioSciences, University of Melbourne, Parkville, VIC 3010, Australia.